Tanggungjawab Bank terhadap Pihak Ketiga yang Merubah PIN Internet Banking dan Mengalihkan Dana Nasabah Ditinjau Dari Undang-undang Perbankan - Amindya Putri, Marina Ayusta (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2020)
ABSTRAK Banks as financial institutions which work based on public trust, as the technology develops, the Internet Banking came as a form of online service that is pused and provided by banks to promote and, at the same time, make transactions online. In addition to providing a convenient way for customers conducting various types of transactions, it does not always have a positive impact because there are cases of customers experiencing data theft committed by the third party that has an impact on thelessen saings amount of the customers, even for a fact that the customer has not done any transaction at before some of their money was gone.The type of research used to explore the case is normative legal research, the nature of the research is descriptive, using secondary data, and data collection methods obtained through document studies or library research. The results of this study indicate that the bank must prioritize the principle of prudence because it concerns the security of customer’s funds that have been entrusted to the bank and this will lead to distrust the uncomfortable and uncertain situationfor the people. Keywords: Internet Banking PIN, Banking, Customer Data.